2007
DOI: 10.1088/0031-9120/42/6/012
|View full text |Cite
|
Sign up to set email alerts
|

European particle physics masterclasses make students into scientists for a day

Abstract: In 2005 the European particle physics masterclasses attracted 3000 students from 18 European countries to visit one of 58 universities and education centres. The participants worked with data from real high energy particle collisions, learned about particle physics, and experienced research and education environments at European universities. In an evaluation of the masterclasses 70% of the participants reported that they learned ‘much’ or ‘very much’ about the organization of scientific research and more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Particle Physics Masterclasses are an established means of bringing high school students into contact with particle physics. Studies have shown that Masterclasses promote young people's interest in modern physics [5]. This successful concept has been adapted by other communities: IceCube Masterclasses have run since 2014, and neutrino Masterclasses with MINERvA data will be launched in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Particle Physics Masterclasses are an established means of bringing high school students into contact with particle physics. Studies have shown that Masterclasses promote young people's interest in modern physics [5]. This successful concept has been adapted by other communities: IceCube Masterclasses have run since 2014, and neutrino Masterclasses with MINERvA data will be launched in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Somado a isso se tem um evento mundial cujo público alvoé estudantes do ensino médio, formados em diferentes sistemas educacionais e com diferentes enfoques noâmbito da abordagem disciplinar e curricular de física. Estudos recentes pautados na participação de estudantes da Europa nesse evento também apontam que a diferença de gênero nãoé fator determinante para o engajamento dos alunos nas atividades do evento e que apesar de estar fixado em um intervalo curto de tempo, promove um maior interesse dos estudantes pelos temas atuais da física [11]. Nessa perspectiva o evento Masterclasses -Hands on se apoia em uma estrutura conceitual e experimental da ciência produzida no LHC e que propomos, no caso do IFUSP, como condução dessas atividades, uma postura de abertura do diálogo que promova outros debates que mostrem-se potenciais para oâmbito da ACT.…”
Section: O Evento Masterclasses -Hands Onunclassified
“…The program aims to convey an authentic picture of the daily life of a scientist, to fascinate students about modern research in physics and to encourage their involvement with science. A refereed evaluation [11] investigated to what extent these objectives are achieved. 1291 Students from 18 European countries were included in an evaluation study in 2005.…”
Section: International Masterclasses -A Successful Programmentioning
confidence: 99%